Think like a freak the authors of Freakonomics offer to retrain your brain - Levitt, Steven D.; Dubner, Stephen J. (William Morrow, an imprint of HarperCollinsPublishers, 2014)
The Freakonomics books have come to stand for something: challenging conventional wisdom; using data rather than emotion to answer questions; and learning to unravel the world's secret codes. Now Levitt and Dubner have gathered up what they have learned and turned it into a practical toolkit for thinking differently -- thinking, that is, like a Freak. Whether you are interested in the best way to improve your odds in penalty kicks, or in major global reforms, here is a blueprint for an entirely new way to solve problems. Along the way, you'll learn how the techniques of a Japanese hot-dog-eating champion can help you, the reason an Australian doctor swallowed a batch of dangerous bacteria, why Nigerian email scammers make a point of saying they're from Nigeria, and why Van Halen's demanding tour contract banning brown M&Ms was really a safety measure. You'll learn why sometimes it's best to put away your moral compass, and smarter to think like a child. You will be given a master class in incentives -- because for better or worse, incentives rule our world. And you will learn to quit before you fail, because you can't solve tomorrow's problem if you aren't willing to abandon today's dud.